Blood shear stress during the cardiac cycle and endothelial cell orientation and polarity in the carotid artery of male and female mice - Nicolas, Nabil; de Tilly, Alexandre; Roux, Etienne (Frontiers in Physiology, 2024)
Blood flow produces fluid shear stress (SS), a frictional force parallel to the blood flow, on the endothelial cell (EC) layer of the lumen of the vessels. ECs themselves are sensitive to this frictional force in terms of directionality and intensity. The aim of this study was to determine the physiological shear stress value during the cardiac cycle and EC polarity and orientation from blood flow in healthy male and female mouse carotid artery. Experimentation is done on anesthetized male and female 8-week-old C5BL/6J mice. In vivo measurements of maximum blood velocity and vessel diameter in diastole and systole were performed on the right common carotid artery by Doppler ultrasound imaging. Blood viscosity (total and plasmatic) and hematocrit were determined on blood samples. For SS calculation, we developed a new method assuming heterogenous blood flow, i.e., a red cell central plug flow surrounded by a peripheral plasma sheath flow, and computing SS from vessel diameter and hemodynamical measurements (maximal blood velocity, hematocrit and plasmatic viscosity). Results were compared with the classical method assuming a homogenous blood flow with constant apparent total blood viscosity. EC polarity and orientation were determined ex vivo on the carotid endothelium by confocal imaging after labeling of the EC nucleus and Golgi apparatus.Diastolic and systolic SS were 6±2.5 Pa and 30±6.5 Pa, respectively. Total blood and plasmatic viscosity was 4±0.5 cP and 1.27 cP, respectively. ECs were polarized and significantly oriented against blood flow. No sex difference was identified.